Paulo Freire: other childhoods for children (2020)
The text analyzes Paulo Freire's contributions on childhood. Considering that childhood was not a central axis of his concerns, this document presents a singular contribution of the teacher, precisely in a minor topic of his work. To this end, a study is made of Freire's own reading of his childhood in Letters to Christine, an autobiographical text in which he dialogues publicly with himself. Likewise, the image of childhood lying there is highlighted and this study is complemented with some references to other works - The Importance of the Act of Reading, That School Called Life, On education: Some dialogues, Learning to Question: A Pedagogy of Liberation, In the Shadow of this Mango Tree, and Pedagogy of Indignation — works in which the educator from Pernambuco presents a conception of childhood and early life that goes beyond the most traditional idea of childhood, as a chronological stage, in order to establish it as a force of life, even, or particularly, in the case of a revolution.